Balanced scorecard for sustainability of Malaysian Higher Education Institutions: Myth or facts? - Mohd Ali, Hairuddin; Ayodele, Lasisi Abass (2017)
The purpose of this study is to explore the relationship between Balanced Scorecard initiatives (BSCI) and organizational climate on the sustainability of higher education institutions. A sample of 272 top administrators at eight selected public universities in Malaysia was selected based on purposive sampling. A full-fledged Structural Equation Modeling Software Analysis of Moment Structures version 20.0 was used as statistical analysis technique in examining the psychometric properties, testing the hypothesis of Balanced Scorecard initiatives, organizational climate on the Sustainability of Malaysian higher education institutions (SMHEI) variables. Using a comprehensive Balanced Scorecard Initiatives theory this paper argues that Balanced Scorecard Initiatives provide a systemic strategy for the achievement of sustainability in Malaysian higher education institutions. The findings reveal that organizational climate has no relationship with sustainability and therefore consistent with previous literature due to communication challenges and decision-making in HEI that needs further attention among the selected eight higher education institutions in Malaysia. This study provides a basis for the future study but the result cannot be generalized for the whole of Malaysia due to the study is limited to peninsular Malaysia only. The framework presented in this study can be used as the basis for the development of general framework of the Balanced Scorecard, organizational climate and in the sustainability of higher education institutions perspectives. This paper indicates the preliminary findings on the Balanced Scorecard Initiatives and it is considered as first kind of research on the SMHEI.